2014
DOI: 10.1177/1470320313515037
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone reduces arterial thrombosis in diabetic rats

Abstract: Introduction: Clinical studies demonstrated the benefits of eplerenone (EPL) in reduction of cardiovascular events in diabetic patients. Since acute myocardial infarction (AMI) and stroke are related to acute intravascular thrombosis, we postulate that the beneficial effects of EPL may result from its antithrombotic action. Materials and methods: Streptozotocin (STZ)-induced diabetic rats were treated with EPL (100 mg/kg/day) for 10 days. Thrombosis in the carotid artery was stimulated electrically. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…32,33 There is also an association between elevated plasma aldosterone and Na + levels with increased incidence of coagulation and thrombotic events, which are mediated by aldosterone-induced AT1R signaling and blocked by mineralocorticoid receptor antagonists. [50][51][52][53] Along these line, thrombosis and occluded pulmonary ar- Figure 4. Effect of chronic hypoxia on circulating aldosterone levels in wild-type (WT) versus Cyp2c44 knockout (Cyp2c44 −/− ) female mice is shown.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 There is also an association between elevated plasma aldosterone and Na + levels with increased incidence of coagulation and thrombotic events, which are mediated by aldosterone-induced AT1R signaling and blocked by mineralocorticoid receptor antagonists. [50][51][52][53] Along these line, thrombosis and occluded pulmonary ar- Figure 4. Effect of chronic hypoxia on circulating aldosterone levels in wild-type (WT) versus Cyp2c44 knockout (Cyp2c44 −/− ) female mice is shown.…”
Section: Discussionmentioning
confidence: 99%
“…A blood morphology test was carried out using the hematological analyzer ScilVet ABC Plus+ (HORIBA ABX, Montpellier, France). A volumetric impedance method of counting blood cells was applied [ 54 ] for determination of white blood cells (WBCs), red blood cells (RBCs), medium cell volume (MCV), medium content of hemoglobin (MCH), medium cell hemoglobin concentration (MCHC), hemoglobin (HGB), platelet count (PLT), as well as automatic calculation of hematocrit (HCT).…”
Section: Methodsmentioning
confidence: 99%
“…In a rat model of thrombosis by vena cava ligation, acute Aldo administration enhanced thrombus burden, an effect that was prevented by co-treatment with eplerenone ( 47 ). Eplerenone also reduced post-carotid injury thrombosis in streptozotocin-induced diabetic rats ( 48 ). Aldo treatment has been shown to decrease bleeding time ( 49 ), induce platelet activation and degranulation, and increase expression of the thrombogenic plasminogen activator inhibitor [PAI-1 ( 50 )], whereas MR inhibitors increase bleeding time ( 49 ), decrease platelet activation ( 50 , 51 ), and inhibit expression of PAI-1, fibrinogen, P-selectin, and IL-1β in a variety of rodent models ( 48 , 51 , 52 ).…”
Section: Mr and Aldo In Plaque Rupture And Thrombus Formationmentioning
confidence: 99%
“…Eplerenone also reduced post-carotid injury thrombosis in streptozotocin-induced diabetic rats ( 48 ). Aldo treatment has been shown to decrease bleeding time ( 49 ), induce platelet activation and degranulation, and increase expression of the thrombogenic plasminogen activator inhibitor [PAI-1 ( 50 )], whereas MR inhibitors increase bleeding time ( 49 ), decrease platelet activation ( 50 , 51 ), and inhibit expression of PAI-1, fibrinogen, P-selectin, and IL-1β in a variety of rodent models ( 48 , 51 , 52 ). Paradoxically, Ducros et al ( 53 ) treated cultured human bone marrow ECs with Aldo and found an increase in the synthesis of the anti-thrombogenic endothelial protein C receptor (EPCR) and an increase in the clotting time of isolated plasma exposed to these ECs.…”
Section: Mr and Aldo In Plaque Rupture And Thrombus Formationmentioning
confidence: 99%